Social Worker Intervention Methods in Oncology: A Case Study in Sincelejo, Colombia - Pérez-Contreras, Blanca; Godin-Díaz, Rubiela; Pérez-Basilio, Andrea Paola; Valdelamar-Nadaff, Juan Carlos (Prospectiva. Revista de Trabajo Social e Intervención Social, 2025)
This article presents social workers’ methods, techniques, and strategies in cancer patients treated in public and private health institutions in Sincelejo, Sucre. The study adopted a qualitative approach with a phenomenological design implemented in a case study modality. Ten social workers with at least one year of experience in clinical oncology were selected. The data collection instrument consisted of a face-to-face semi-structured interview and an asynchronous data collection, using a Google Forms form as a guide. The results emphasize preference in the application of individual methods, such as control consultations, psychoemotional follow-up, motivational and care talks; in the family, techniques such as socioeconomic study, visits, and home care stand out, as well as resources management for families in vulnerable conditions, through governmental and non-governmental organizations, are highlighted. Community-based approaches are being uses to mitigate risk factors and promote early detection. An active participation of the Social Worker as a member of the health care team is concluded, who provides emotional and social support to the patient and their family, provides detailed information on the treatment process, develops personalized intervention plans, and integrates the family into the patient’s treatment and recovery process.